2014
DOI: 10.1007/s10811-014-0453-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IMTA-produced seaweeds (Gracilaria, Porphyra, and Ulva) as dietary ingredients in Nile tilapia, Oreochromis niloticus L., juveniles. Effects on growth performance and gut histology

Abstract: The present study evaluated the effects of the inclusion of three seaweeds, Gracilaria vermiculophylla (GRA), Porphyra dioica (POR), and Ulva spp. (ULV), as dietary ingredients for Nile tilapia (Oreochromis niloticus) juveniles, on the growth performance, body composition, and gut histology. Three experimental diets (GRA, POR, and ULV) were formulated to replace 10 % of whole diet by each of the three seaweeds. A control diet (CTRL) was used, without inclusion of any seaweed. Diets were fed to triplicate group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 82 publications
(95 reference statements)
6
58
1
1
Order By: Relevance
“…All experimental diets were suitable for the fish; that is, the levels of inclusion of protein in diets of Nile tilapia juveniles had no detrimental effect on survival, weight gain, daily growth index and daily voluntary feed intake. The fish growth performance was similar to other studies (Abdel‐Tawwab et al, ; El‐Saidy & Gaber, ; Hernández et al, ; Silva et al, ), particularly taking into account that the experimental diets contained no fish meal nor fish oil in their formulation.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…All experimental diets were suitable for the fish; that is, the levels of inclusion of protein in diets of Nile tilapia juveniles had no detrimental effect on survival, weight gain, daily growth index and daily voluntary feed intake. The fish growth performance was similar to other studies (Abdel‐Tawwab et al, ; El‐Saidy & Gaber, ; Hernández et al, ; Silva et al, ), particularly taking into account that the experimental diets contained no fish meal nor fish oil in their formulation.…”
Section: Discussionsupporting
confidence: 87%
“…Feed conversion ratio for Nile tilapia found in the literature varies significantly, which is likely due to discrepancies in experimental diets and conditions, such as feed quality (physical and nutritional), feeding regime, fish age and size. Considering fish size and dietary protein sources (mainly plant ingredients), the FCR values in the present study are lower or within the values found in similar studies (Abdel‐Tawwab et al, ; El‐Saidy & Gaber, ; Hernández et al, ; Silva et al, ). Based on the overall growth performance and the FCR observed in the present study, it is implied that the dietary protein levels can be reduced down to 300 g/kg diet without hindering fish growth performance and FCR.…”
Section: Discussionsupporting
confidence: 75%
“…The shorter villi in GL-90 and GL-120 groups might be attributed to the presence of several ANFs in Gracilaria species, as proposed by Silva et al (2015). It has been demonstrated that Gracilaria species contain several ANFs (Benevides et al, 1998) which are resistant to proteolytic hydrolysis by digestive enzymes and harmful to the gut (Bardocz, Ewen, Grant, & Pusztai, 1995).…”
Section: Discussionmentioning
confidence: 81%
“…Morphological examinations carried out on Nile tilapia ( O. niloticus ) showed there was a reduction in both proximal intestinal diameter and villi length (Silva et al . ). This was particularly evident after being fed for 84 days on 10% inclusion diet.…”
Section: Macroalgae In Fish Dietsmentioning
confidence: 97%